Do Superordinate Identification and Temporal/Social Comparisons Independently Predict Citizens’ System Trust? Evidence From a 40-Nation Survey - Caricati, Luca; Owuamalam, Chuma Kevin; Bonetti, Chiara (Frontiers in Psychology, 2021)
Do superordinate in-group bias as well as temporal and social comparisons offer standalone explanations for system justification? We addressed this question using the latest World Value Survey (7th Wave), combining the responses of 55,721 participants from 40 different nations. Results from a random slope multilevel model showed that superordinate (national) identification, temporal comparison (i.e., the outcomes of an individual relative to those of his/her parents at different time points), and social comparison (based on income levels) were independent and positive predictors of system justification. Specifically, system justification increased when national identification was high, when income increased (i.e., the socioeconomic comparison was positive), and when the outcomes of citizens improved relative to the outcomes of their parents at relevant time points (i.e., the temporal comparison was positive). Incidentally, we also observed an interaction between national identification and temporal comparison (but not with social comparison), indicating that positive temporal comparison seemed to have a reduced effect (but still significant) for highly identified citizens. These results are supportive of the social identity approach to system justification and suggest that support for societal systems is a positive function of people’s personal and group interests.